Relationship between periodontal disease and systemic lupus erythematosus - Carlos Marcelo da Silva Figueiredo; Henrique Guilherme de Castro Teixeira; José Márcios Falabella; Márcio Eduardo Vieira Falabella; Lígia de Araújo Ramos Sales (Faculdade São Leopoldo Mandic, 2008)
﻿There has been a constant search for a definition of criteria of susceptibility to periodontal diseases in modern Periodontology, as it is of the greatest importance, since it enables improvements in prevention, early diagnosis, treatment and prognosis of this disease. It is in this context that this literature review was conducted, with the object of verifying whether there is a greater propensity to periodontal disease in individuals with systemic lúpus erythematosus, a chronic inflammatory disease, whose pathogenesis presents some characteristics similar to those of the pathogenesis of periodontal disease. The majority of existent studies about the subject have pointed towards the possible existence of such susceptibility. Nevertheless, the relationship between this autoimmune disease and periodontal disease has not yet been well established, and the mechanisms by which the systemic disease influences the periodontal health of patients affected with it are not yet clear. Further studies are required in order to affirm that individuals with systemic lúpus erythematosus are a group of risk for the development of periodontal disease, and in order to understand the mechanisms involved in this possible relationship of susceptibility.